Culture in health care in the Republic of Serbia - Stevanović Ivan; Gajić-Stevanović Milena; Aleksić Jovana (Serbian Medical Society - Dental Section, Belgrade, 2015)
Culture encompasses entire societies, influences everything we feel, see, do and believe and shape the way we approach the world around us. Culture is an inseparable part of human existence and as such an important part of health and health care. The aim of this paper was to present specific forms of culture in health care that have influence on the quality of health care system, as well as to investigate in which capacity is work on culture in the health care system in Serbia represented. National and international literature and documentation was processed using analytical methods - observation and comparative method. Health culture as responsibility of health care users and culture in health care as responsibility of health care employees are key factors in improving the health system in Serbia. The most important step has been made with the strategic plan of the Government of the Republic of Serbia in 2010, however, everyone has to accept and understand the importance of culture in health care and apply its rules into the practise.